2010
DOI: 10.2174/157489010791515386
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective, Observation Study: Quantitative and Qualitative Effect of Ezetimibe and HMG-CoA Reductase Inhibitors on LDL-Cholesterol: Are There Disappearance Thresholds for Small, Dense LDL and IDL?

Abstract: Lipid profiles were evaluated for 281 dyslipidemia patients treated with HMG-CoA reductase inhibitors (statins) for 2 years. The efficacy and safety of ezetimibe 10 mg/day one-year add-on therapy were also retrospectively evaluated. The results show that in 281 dyslipidemia patients with a mean low-density lipoprotein-cholesterol (LDL-C) level of 120 mg/dl or greater, ezetimibe 10 mg/day administration reduced LDL-C levels to 90 mg/dl or below. Patients who had been treated with one of six statins (pravastatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Some studies have demonstrated that several statins reduce not only LDL but also sdLDL [8]. However, we have believed that we need to lower sdLDL further [9].…”
Section: Introductionmentioning
confidence: 98%
“…Some studies have demonstrated that several statins reduce not only LDL but also sdLDL [8]. However, we have believed that we need to lower sdLDL further [9].…”
Section: Introductionmentioning
confidence: 98%